PUBLIKASI LAPORAN KEUANGAN PEMERINTAH DAERAH (LKPD114) MELALUI INTERNET (IFLGR) DAN FAKTOR-FAKTOR YANG MEMPENGARUHI - Daniel Wicaksono; Adhi Prabowo (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2016)
This study focuses on the application of Internet Financial Local Goverment Report (IFLGR) and it’s influencing factors after the issnance of legislation of openness of public information and the influences significenly on the Minister of Home Affairs No.188.52 / 1797 / SJ in 2012, in which is all about the effort embodiment of Good Government. Selected population in this study were all provinces in Indonesia which publishing budget transparency on their official website. Selected factors is have consist ofpolitic competition, total assets of local goverment (kay), leverage (lev), the degree of independence (tk), the level of GDP (pd), and BPK audit opinion. By using binary logistic regression with alpha 5%. The results show that the level of independence influential in the implementation of Internet Financial Local Goverment Report (IFLGR), while the rests of variables do not. Key word: IFLGR, politic competition, total assets of local goverment, leverage, the degree of independence, the level of GDP, and BPK audit opinion